Attention driven game with brain-computer interface - Sun, Shengjie (2014)
From physical keyboard to touch keyboard, from mouse to touch pad, and the many latest wearable controllers, people are looking for different ways to interact with computers for years. Researches have been done on Electroencephalogram (EEG) based technology, and used it in neurofeedback games and brain-computer interface. Although the brain-computer interface still can’t provide a smooth control as keyboard or joystick to games on market like call of duty, need for speed etc. Such technologies could also be used in simple entertainment and medical applications. In this report, I will review on possible EEG activities associated with concentration level indication, signal processing process, as well as a concentration driven game design and implementation.